Design and Implementation of Environmental Performance Rating and Public Disclosure Programs : A Summary of Issues and Recommendations Based on Experiences in East Asian Countries Experiences in East Asian Countries - Gozun, Elisea G.; Laplante, Benoit; Wang, Hua (2012)
A number of countries around the world have in recent years implemented environmental performance rating and public disclosure programs, and, where evidence is available, these programs have been shown to induce pollution reduction. Based on previous research and practical experiences from several Asian countries, this paper provides a systematic review and discussion of the practical issues involved in designing and implementing environmental performance rating and public disclosure programs, including the legal and institutional framework, scope and coverage determination, performance rating methodology, data collection and verification, disclosure strategy, credibility assurance, program set-up and expansion, etc. The authors offer comments and recommendations, where appropriate, for environmental regulators to tackle these practical issues. The reviews and discussions are intended to be concise, simple, and systematic, and alternative options are discussed in a succinct manner, so that they can be readily used by interested environmental regulators and researchers.